GAMBARAN KEPATUHAN MASYARAKAT MAWANG KELOD DALAM MENERAPKAN PROTOKOL PENCEGAHAN COVID-19 DI TEMPAT UMUM - Sukawana, I Wayan; Sukarja, I Made (Coping: Community of Publishing in Nursing; Vol 9 No 2 (2021): April 2021DO - 10.24843/coping.2021.v09.i02.p11, 2021)
Covid-19 is a disease that is very easily transmitted through droplets and aerosols containing the SARS-CoV-2 virus. Covid-19 transmission can be prevented by complying the Covid-19 preventive health protocol. This study aims to obtain an overview of community compliance in implementing the Covid-19 prevention protocol. Respondents in this study were 60 people from Mawang Kelod Adat village who were taken by consecutive sampling technique. Data was collected by observing people's behavior in implementing the Covid-19 prevention protocol. The results of the study found that 30.0% of respondents used masks according to the standard, 5% who washed their hands when they arrived at the place observed, and 16.7% who kept a distance of more than 1 meter. Only 1.7% of respondents who adhere to the three types of COVID-19 prevention protocols.